2010
DOI: 10.1007/s11105-010-0277-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity in Lemons and Some of Their Relatives Based on SRAP and SSR Markers

Abstract: Genetic diversity was evaluated by sequencerelated amplified polymorphism (SRAP) and simple sequence repeat (SSR) markers among 45 lemons (Citrus limon (L.) Burm. f.), five citrons (Citrus medica L.), four rough lemons (Citrus jambhiri Lush), and two Citrus volkameriana accessions. Twenty-one SRAP primer combinations produced a total of 141 (77%) polymorphic fragments with an average of 6.7 fragments per primer combinations whereas 13 SSR primers produced a total of 26 (76%) polymorphic fragments with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
(60 reference statements)
1
22
0
Order By: Relevance
“…At the same way, C. volkameriana was clustered with rough lemon as in the RAPD (Luro et al, 1992) and SCAR (Nicolosi et al, 2000) based studies. It is reported there was low level of polymorphism among most of lemons derived via clonal selection whereas higher genetic diversity was found in lemons which had hybrid origin (Uzun et al, 2011b). Genetic similarity of 45 lemons included both mutation and hybrid origin was notified between 0.80-1.00 (Fig.…”
Section: Genetic Diversity In Lemon and Relatives (Citron Rough Lemomentioning
confidence: 93%
See 4 more Smart Citations
“…At the same way, C. volkameriana was clustered with rough lemon as in the RAPD (Luro et al, 1992) and SCAR (Nicolosi et al, 2000) based studies. It is reported there was low level of polymorphism among most of lemons derived via clonal selection whereas higher genetic diversity was found in lemons which had hybrid origin (Uzun et al, 2011b). Genetic similarity of 45 lemons included both mutation and hybrid origin was notified between 0.80-1.00 (Fig.…”
Section: Genetic Diversity In Lemon and Relatives (Citron Rough Lemomentioning
confidence: 93%
“…Similarly, Gulsen and Roose (2001), reported that similarity level of citron and lemon-rough lemon group was 0.65 based on their ISSR data. On the other hand, according to Uzun et al (2011b), genetic similarity among lemons and rough lemon-C. volkameriana group was 0.80. Rough lemons and C. volkameriana were closely related.…”
Section: Genetic Diversity In Lemon and Relatives (Citron Rough Lemomentioning
confidence: 94%
See 3 more Smart Citations